2023
DOI: 10.3390/cells12101434
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Cholesterol Metabolites in a Bile Acid Synthetic Pathway Drive Nonalcoholic Fatty Liver Disease: A Revised “Two-Hit” Hypothesis

Abstract: The rising prevalence of nonalcoholic fatty liver disease (NAFLD)-related cirrhosis highlights the need for a better understanding of the molecular mechanisms responsible for driving the transition of hepatic steatosis (fatty liver; NAFL) to steatohepatitis (NASH) and fibrosis/cirrhosis. Obesity-related insulin resistance (IR) is a well-known hallmark of early NAFLD progression, yet the mechanism linking aberrant insulin signaling to hepatocyte inflammation has remained unclear. Recently, as a function of more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 147 publications
0
3
0
Order By: Relevance
“…It is possible that the incomplete cholesterol breakdown due to HSDL2 depletion may have led to the buildup of cholesterol intermediates in the mitochondria. Numerous studies now show that mitochondrial accumulation of cholesterol and oxysterols impairs mitochondrial function (71,72). Because there are significant differences in the catabolic intermediates produced from cholesterol degradation between immortalized and normal hepatocytes (73)(74)(75), differences in the production and recycling of cholesterol derivates and FXR ligands could have contributed to the alteration of mitochondrial function and FXR activation in these experiments.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that the incomplete cholesterol breakdown due to HSDL2 depletion may have led to the buildup of cholesterol intermediates in the mitochondria. Numerous studies now show that mitochondrial accumulation of cholesterol and oxysterols impairs mitochondrial function (71,72). Because there are significant differences in the catabolic intermediates produced from cholesterol degradation between immortalized and normal hepatocytes (73)(74)(75), differences in the production and recycling of cholesterol derivates and FXR ligands could have contributed to the alteration of mitochondrial function and FXR activation in these experiments.…”
Section: Discussionmentioning
confidence: 98%
“…Overaccumulated lipids can be oxidized, esterified and restored in the liver, leading to metabolite leakage such as phospholipids, triglycerides, fatty acids and so on [ 57 ]. In order to further explore the regulation of lipid metabolism and inflammation process by SZ-As, an untargeted lipidomics study was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Short-chain fatty acids (SCFAs) are a class of saturated and fatty acids produced by intestinal flora through fermentation of soluble dietary fiber, including acetate, propionate, and butyrate. Zhao, T. et al found that butyrate supplementation could inhibit the activity of NADH oxidase in the ETC of MAFLD patients, increase the concentration of potassium ions in the mitochondria, maintain the mitochondrial membrane potential, and delay the development of MAFLD [130,176]. Acetate and propionate mainly maintain the intestinal barrier and reduce the release of inflammatory factors such as IL-6 [177].…”
Section: Bile Acids (Bas) and Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%